2020
DOI: 10.1038/s41467-020-19034-y
|View full text |Cite
|
Sign up to set email alerts
|

21-nt phasiRNAs direct target mRNA cleavage in rice male germ cells

Abstract: In grasses, phased small interfering RNAs (phasiRNAs), 21- or 24-nucleotide (nt) in length, are predominantly expressed in anthers and play a role in regulating male fertility. However, their targets and mode of action on the targets remain unknown. Here we profile phasiRNA expression in premeiotic and meiotic spikelets as well as in purified male meiocytes at early prophase I, tetrads and microspores in rice. We show that 21-nt phasiRNAs are most abundant in meiocytes at early prophase I while 24-nt phasiRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 58 publications
(96 reference statements)
0
64
0
Order By: Relevance
“…This may have resulted in reduced precision, particularly in the case of Arabidopsis in which most tools performed their worst in terms of precision. In the case of rice, however, we utilized well staged low-input sRNA and PARE sequencing libraries generated in triplicates from small amounts of tissue (Jiang et al, 2020). These tissue-specific datasets may provide cleaner results with less noise in the PARE data than what was found in the Arabidopsis and maize libraries resulting in the best predictions for all tools.…”
Section: Discussionmentioning
confidence: 99%
“…This may have resulted in reduced precision, particularly in the case of Arabidopsis in which most tools performed their worst in terms of precision. In the case of rice, however, we utilized well staged low-input sRNA and PARE sequencing libraries generated in triplicates from small amounts of tissue (Jiang et al, 2020). These tissue-specific datasets may provide cleaner results with less noise in the PARE data than what was found in the Arabidopsis and maize libraries resulting in the best predictions for all tools.…”
Section: Discussionmentioning
confidence: 99%
“…One study in pummelo predicted and verified targets in trans with gene ontologies of broad terms but also including PCD and pollen development (Fang et al 2020). By now, two pioneering study in rice meiocytes finally found indeed RNA degradation of target genes of reproductive 21nt-phasiRNAs (Jiang et al 2020;Zhang et al 2020c). In rice meiocytes, target genes were enriched for carbohydrate biosynthesis and metabolism, and also included OsDMC1B, a meiotic gene (Jiang et al 2020).…”
Section: Tasirnasmentioning
confidence: 98%
“…By now, two pioneering study in rice meiocytes finally found indeed RNA degradation of target genes of reproductive 21nt-phasiRNAs (Jiang et al 2020;Zhang et al 2020c). In rice meiocytes, target genes were enriched for carbohydrate biosynthesis and metabolism, and also included OsDMC1B, a meiotic gene (Jiang et al 2020). Another study gained insight on genes targeted for degradation in rice anthers through degradome data from whole rice spikelets of WT and of mutants in MEL1, the rice AGO5 which binds phasiRNA.…”
Section: Tasirnasmentioning
confidence: 99%
See 2 more Smart Citations